2015
DOI: 10.1016/j.paid.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Cognitions as mediators in the relationship between self-compassion and affect

Abstract: Previous studies suggest that self-compassion is related to numerous facets of mental health, but the role of cognitions in this relationship remains unknown. To examine the mediating role of cognitions in the relationship between self-compassion and anxiety, depression, and life satisfaction when controlling for self-esteem in Japanese people, we conducted two studies. Study 1 (N = 231) examined the relationship between self-compassion and affect by modeling negative automatic thoughts as a mediator; Study 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 63 publications
7
34
0
3
Order By: Relevance
“…Their investigation showed that self-compassion was positively correlated with positive affect and negatively correlated with negative affect Neff & Vonk, 2009) while the same results revealed by Arimitsu & Hofmann (2015), arguing that self-compassion leads to increase of positive automatic thoughts which in turn lead to higher levels of life satisfaction and lower levels of anxiety. So, it is so far confirmed by literature that self-compassion is associated with reduced negative affect and increased positive affect and happiness .…”
Section: Positive and Negative Affectmentioning
confidence: 74%
See 1 more Smart Citation
“…Their investigation showed that self-compassion was positively correlated with positive affect and negatively correlated with negative affect Neff & Vonk, 2009) while the same results revealed by Arimitsu & Hofmann (2015), arguing that self-compassion leads to increase of positive automatic thoughts which in turn lead to higher levels of life satisfaction and lower levels of anxiety. So, it is so far confirmed by literature that self-compassion is associated with reduced negative affect and increased positive affect and happiness .…”
Section: Positive and Negative Affectmentioning
confidence: 74%
“…To state it differently, people who are more self-compassionate have the tendency to make more positive automatic thoughts (Arimitsu & Hofmann, 2015) and that consequently results in higher levels of life satisfaction. Hence, they are more capable of dealing more effectively and coping better with their possible failures, mistakes and personal weaknesses, as they maintain a positive attitude towards those conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Further, grateful people have a positive attitude toward themselves and others and they generally think that life is meaningful, understandable, and manageable ( Lambert et al, 2009 ). Certain researchers believe that positive emotional factors play roles in the influence of self-compassion on the negative psychological outcomes of post-trauma victims ( Arimitsu and Hofmann, 2015 ). Therefore, gratitude may be another mediator between self-compassion and suicide risk.…”
Section: Introductionmentioning
confidence: 99%
“…Por um lado, verificou-se que a maior frequência de pensamentos automáticos negativos se associa a níveis mais elevados de isolamento, sobreidentificação e autocritica (avaliados pela escala SCS). De facto, apesar de, do nosso conhecimento, não existirem estudos sobre este tópico com a população perinatal, os estudos com a população geral demonstram que existe uma associação negativa entre a autocompaixão e pensamentos automáticos negativos (Arimitsu & Hofmann, 2015) e que, concordantemente, níveis mais elevados de autocompaixão se refletem na diminuição dos pensamentos negativos (Stuntzner, 2014). Também as correlações positivas encontradas entre a EPANP, os pensamentos automáticos negativos gerais e a sintomatologia depressiva se evidenciam congruentes com o esperado e com os resultados encontrados noutros estudos (e.g., Hall & Papageorgiou, 2005).…”
Section: Discussionunclassified
“…Assim, este estudo tem como principal objetivo a adaptação do PNTQ (em português, Escala de Pensamentos Automáticos Negativos Pós-Parto) para a população portuguesa e o estudo das suas propriedades psicométricas. Estudos recentes apontam para uma correlação positiva entre pensamentos automáticos negativos no pós-parto e sintomatologia depressiva (Hildebrant, 2013) e pensamentos automáticos negativos gerais (Hall & Papageorgiou, 2005), bem como uma correlação negativa com a autocompaixão (Arimitsu & Hofmann, 2015), pelo que a associação com estas variáveis foi também investigada no contexto do estudo das propriedades psicométricas da escala.…”
Section: Introductionunclassified